Synergic Crosstalk between Inflammation, Oxidative Stress, and Genomic Alterations in BCR-ABL-Negative Myeloproliferative Neoplasm - Alessandro Allegra; Giovanni Pioggia; Alessandro Tonacci; Marco Casciaro; Caterina Musolino; Sebastiano Gangemi (MDPI AG, 2020)
Philadelphia-negative chronic myeloproliferative neoplasms (MPNs) have recently been revealed to be related to chronic inflammation, oxidative stress, and the accumulation of reactive oxygen species. It has been proposed that MPNs represent a human inflammation model for tumor advancement, in which long-lasting inflammation serves as the driving element from early tumor stage (over polycythemia vera) to the later myelofibrotic cancer stage. It has been theorized that the starting event for acquired stem cell alteration may occur after a chronic inflammation stimulus with consequent myelopoietic drive, producing a genetic stem cell insult. When this occurs, the clone itself constantly produces inflammatory components in the bone marrow; these elements further cause clonal expansion. In BCR-ABL1-negative MPNs, the driver mutations include JAK 2, MPL, and CALR. Transcriptomic studies of hematopoietic stem cells from subjects with driver mutations have demonstrated the upregulation of inflammation-related genes capable of provoking the development of an inflammatory state. The possibility of acting on the inflammatory state as a therapeutic approach in MPNs appears promising, in which an intervention operating on the pathways that control the synthesis of cytokines and oxidative stress could be effective in reducing the possibility of leukemic progression and onset of complications.